Detection and estimation of Mastigimas anjosi (Hemiptera: Calophyidae) populations on Cedrela fissilis trees - Prado, Marcelle C. Do N.; Giuliani, Graziella K.F.; Ghiotto, Thais C.; Carmo, Janaina B. do; Guerreiro, Júlio C.; Prado, Evandro P. [UNESP]; Pogetto, Mario H.F. Do A.D.; Masson, Marcus V.; Tavares, Wagner De S.; Wilcken, Carlos F. [UNESP]; Zanuncio, José C.; Ferreira-Filho, Pedro J. (The Royal Society, 2022)
Mastigimas anjosi is an important pest of Cedrela fissilis in the southeastern and southern regions of Brazil. The objective of the present study was to investigate the effect of the temperature, relative humidity, rainfall and natural enemies on the flight activity of adults and the movement of M. anjosi nymphs, with two sampling methods, yellow sticky traps and direct collections on the leaves of C. fissilis trees. The sex ratio of this pest was also assessed. The number of M. anjosi individuals was negatively correlated with the minimum and maximum temperatures, with a population peak in late May and early June 2017. The numbers of individuals of this psyllid was positively correlated with the relative humidity and rainfall. Larvae and adults of Cycloneda sanguinea, Hippodamia convergens adults and Atopozelus opsimus nymphs and adults preyed upon M. anjosi adults and nymphs on C. fissilis leaves in the field. Mastigimas anjosi sex ratio was 0.46. Information about sampling methods of M. anjosi and its natural enemies is presented and can contribute to the integrated management of this pest in the field.
Keywords: biological control; forest pest; monitoring; population dynamics; sticky trap; tropical cedar